Copper-Catalyzed Cross-Dehydrogenative Coupling of α-Hydroxy Esters with Nitromethane - Xiao, Lili; Jiang, Jin (Synlett, 2021)
An efficient copper-catalyzed tandem oxidation/nitroaldol reaction of hydroxyl compounds with nucleophiles is developed. In this work, β-nitro-α-hydroxy esters were prepared via cross-dehydrogenative coupling reaction using α-hydroxy esters as hydroxy compounds and nitromethane as a nucleophile. The reaction is believed to undergo an oxidation of the hydroxy group and then an addition of the generated carbonyl group. It is an example of CDC reactions related to hydroxy compounds via carbonyl intermediates.
Keywords: alcohols; copper; cross-coupling; dehydrogenation; nucleophilic addition